(3JNQjL CMGOjK GdCPcGQs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO ajg ef BNQ GdeLdS GdKGfi hGdCQHYjf HYO GdNeSeGFI hgh GdKGfi hGdYTQhf HYO GdJSYeGFi ef GdCeGdi GdeUQjI bhdg Yf GdfHi Udi Gddg Ydjg hSde bGd eGA ReRe TaGA ef cd OGA hSfOg VYja LOkG s
(3BNQgG (B:s
(3BNQ GdehLhO efg ai Chd GdeLdS GdKGdK hGdCQHYjf HYO GdSJeGFI Hbhd (B: (3abGd dg GdfHi Udi Gddg Ydjg hSde hYdjgG EQLY aUd aUd aEfc de JUd aQLY GdQLd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs